Food Fit for Swine, Nourishment, and Gift from God: On Cultural Transfers at the Edge of the Atlantic Area - Křížová, Markéta (Dějiny – teorie – kritika, 2019)
The article focuses on the issue of indirect cultural transfers in the Atlantic area in Early Modern Era, mainly transfers of material culture (culinary practices) and their broader consequences. As a case study, the author uses the introduction of potatoes into the Lands of the Bohemian Crown in the eighteenth century. Another aim of this article is to tests the viability of concepts originally proposed for the description of cultural transfers in non-European regions (transculturation, contact zone, creolisation) for the study of cultural transfers in areas not characterised by an immediate clash of cultures in the course of conquest and colonisation of overseas territories. The main aim of the text is to highlight the fact that the ‘great frontier’ of Early Modern global transformation of cultures and lifestyles reached even the apparently marginal areas of Central Europe.